2017
DOI: 10.1002/jrs.5163
|View full text |Cite
|
Sign up to set email alerts
|

Graphite‐bearing mineral assemblages in the mantle beneath Central Aldan superterrane of North Asian craton: combined confocal micro‐Raman and electron microprobe characterization

Abstract: Mantle‐derived lherzolitic and harzburgitic Cr‐pyropes from lamprophyres of the Chompolo field (Central Aldan superterrane, North Asian Craton) were studied using micro‐Raman spectroscopy and electron microprobe microanalysis. These garnets enclose graphite coexisting with forsterite, diopside, Ba‐Cl‐phlogopite, tschermakite, rutile, magnesiochromite, Mg‐ilmenite, apatite, chalcopyrite, dolomite, magnesite and lindsleyite inclusions. The PT conditions of residence of graphite‐bearing assemblage in the mantle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 92 publications
2
19
0
Order By: Relevance
“…Although high-pressure carbonates, K8Ca3(CO3)7 and K2Ca3(CO3) 4 have not yet been found in diamonds, their high melting points, >1200 and >1300 °C, respectively, do not exclude the possibility of their со-crystallization with diamond and their entrapment as mono-and polymineral inclusions ( Figure 6). [35] compared with mantle adiabat [64] and P-T range of diamond growth in the lithospheric mantle [56].…”
Section: Minerals 2019 9 X For Peer Review 13 Of 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Although high-pressure carbonates, K8Ca3(CO3)7 and K2Ca3(CO3) 4 have not yet been found in diamonds, their high melting points, >1200 and >1300 °C, respectively, do not exclude the possibility of their со-crystallization with diamond and their entrapment as mono-and polymineral inclusions ( Figure 6). [35] compared with mantle adiabat [64] and P-T range of diamond growth in the lithospheric mantle [56].…”
Section: Minerals 2019 9 X For Peer Review 13 Of 20mentioning
confidence: 99%
“…Presence of crystalline carbonates at different mantle levels follows from the occurrence of magnesite, dolomite, calcite, and/or aragonite in spinel peridotite and eclogite xenoliths [1][2][3], as primary 2 of 20 inclusions in Cr-pyropes derived from 100-130 km depth [4,5], and as inclusions in diamonds derived from the base of the continental lithosphere and deeper levels [6][7][8][9][10][11][12][13]. Ca-Mg carbonates also appear as rock-forming minerals and/or as inclusions in high-pressure minerals in diamondiferous ultrahigh-pressure (UHP) metamorphic rocks exhumed from 150-250 km depths [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Nikolenko et al report on graphite‐bearing mineral assemblages in the mantle beneath Central Aldan superterrane of the North Asian craton using combined confocal micro‐Raman and electron microprobe characterization. The mineralogy of inclusions in the studied garnets strongly suggests metasomatism by carbon‐rich agents in the lithospheric mantle of the Central Aldan superterrane, which was coeval with the formation of graphite inclusions and the host pyropes . Sakurai et al used micro‐Raman spectroscopy to study microdroplets containing sulfate in the Dome Fuji deep ice core in Antarctica.…”
Section: Art and Archaeologymentioning
confidence: 99%
“…The evolution of Raman spectra during weathering of carbonaceous material of shungite rocks (Karelia, Russia) was investigated by Chazhengina and Kovalevski. The first findings of graphite‐bearing mineral assemblages in the mantle beneath Central Aldan superterrane of North Asian craton were presented by Nikolenko et al and Shchepetova et al and demonstrated that the origin of forbidden mineral assemblage coesite + disordered graphite in diamond‐bearing ultrahigh‐pressure metamorphic rocks is not related to partial diamond graphitization processes.…”
Section: Raman Spectroscopy and Carbonaceous Materialsmentioning
confidence: 99%